'Mother knows best': Maternal oviposition effects of a range‐expanding insect herbivore degrade coastal wetlands by targeting juvenile foundation plant species. (5th August 2022) - Ning, Zhonghua; Chen, Cong; Cui, Baoshan; Zhang, Yihui; Xie, Tian; Wang, Qing; Zhu, Zhenchang; Bai, Junhong; Bouma, Tjeerd J.
Abstract: Species range expansion induced by climate change and human activities threaten native populations and communities across the biosphere. Insect herbivores, important consumers of plants, are known to expand or contract their range under global change, with potential consequences to the newly reached environment. The selection of oviposition sites by herbivorous insects could notably impact offspring performance. However, the role of such effects in impacting the receiving ecosystem has been rarely explored. Here, we provide the first evidence showing that a terrestrial range‐expanding phytophagous wood‐borer moth ( Zeuzera leuconotum Butler) heavily attacked the saplings of a foundation plant species tamarisk ( Tamarix chinensis ) in salt marshes. Long‐term field surveys and laboratory behaviour experiments revealed that the oviposition preference of adult females was beneficial to their larval performance. The preference to oviposit on young branches of the new host plants, which were often softer and contained enough nutrients for larval development, indicates that females could still make the right choice on novel host‐plants. This finding supports the 'mother knows best' hypothesis that female insects will evolve to oviposit on hosts on which their offspring fare best. Consequently, the survival of host‐plant saplings decreased dramatically under this top‐down control, revealing that herbivory of this range‐expanding insect has a profound negative impact on the recruitment and succession of coastal foundation species, thereby potentially leading to saltmarsh degradation. These findings highlight the importance of the maternal oviposition effects in range‐expanding insects and how these populations can establish using novel host‐plants and threaten coastal wetlands.